Adiwiyata schools: obstacles and expectations of environmental culture implementation at state junior high schools in Palembang - Azizah Husin; Muhammad Faisal; Dini Purwaningsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Adiwiyata School is an award from the Ministry of Education and Ministry of Environment and Forestry for schools that cultivate pro-environmental behaviour. The cultivation of such behaviour requires the support of related facilities and infrastructures. This study aimed at determining the obstacles and expectations of Adiwiyata Schools in cultivating pro-environmental culture. It is a descriptive qualitative study the research subjects of which were six people from three Adiwiyata Schools in Palembang. Their positions at their respective schools included Principal, Vice-Principal and Adiwiyata Implementation representatives. The data were collected through interviews, observations and documentations and were analyzed using data reduction, data verification, and conclusions. The results showed that the obstacles included unavailable funds for the provision and maintenance of infrastructure and facilities, inadequate integration of environmental care toward schools’ subjects, diverse students’ perception toward Adiwiyata schools, and insufficient training in implementing the 3 R's (reduce, reuse, recycle). Furthermore, the expectations included better funding for the provision and maintenance, and more comprehensive technical skills guidance of the 3 Rs from the Adiwiyata school evaluator team.